Independence of active substance profiles from the pulse response experimental procedure. Issue 10 (23rd August 2013) - Phanawadee, Phungphai; Pongboutr, Nattapong; Yablonsky, Gregory S.; Constales, Denis; Jarungmanorom, Chukiat; Soikham, Watcharin; Limtrakul, Jumras
Significance The described computational experiment focuses on producing a controlled catalyst activity distribution. Using TAP technique, the activity profile on the solid catalytic material surface is created by adsorption of pulsed feed gas or the like process and is controlled by the total amount of pulsed gas following the coincidence property. The coincidence property is also applicable for other diffusion + irreversible adsorption processes like wet impregnation to prepare catalyst with nonuniform distribution of catalytic material. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3574–3577, 2013